Dysbiotic aspects of pathogenesis and antidysbiotic prophylactics of experimental nephropathy - A. P. Levitsky; A. I. Gozhenko; V. T. Stepan; M. F. Jarynich (Kazimierz Wielki University, 2017)
The aim:  To determine the role of dysbiosis in pathogenesis and antidysbiotic prophylactics of experimental nephropathy. The materials and methods:  Pathogens, which were used: hydrazine sulfate, cyclophosphan, prednisolone, lincomycin, lipopolysaccharide. Antidysbiotic means, which were used: quertulin, quertulin-gel, lequin, lecasil, Biotrit-gel, grapes-gel. Nephropathy was made into rats by the pathogens introduction. The activity of lysozyme, elastase, urease and content of malonic dialdehide were determined into kidneys. The degree of dysbiosis were determined by ration of urease activity to activity of lysozyme. The findings: The whole of pathogens were raised the activity of elastase, urease and content of malonic dialdehide but were lowered the activity of lysozyme into kidney. The antidysbiotic means were raised the activity lysozyme, but were lowered the activity elastase, urease the content of malonic dialdehide and the degree of dysbiosis. Lipopolysaccharide was more active than the rest of pathogens. The conclusion: The must force pathogen for kidney is lipopolysaccharide particular by oral application. The dysbiosis is important in the nephropathy pathogenesis. The antidysbiotic means have nephroprotective action.